PENGARUH ONLINE CUSTOMER REVIEW DAN PRICE CONSCIOUSNESS TERHADAP PURCHASE INTENTION DI MARKETPLACE SHOPEE (STUDI PADA MAHASISWA UNIVERSITAS RIAU) - Nurfauzuliya, Atika Putri; Heriyanto, Meyzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Abstract: This study aims to determine the effect of online customer reviews and price consciousness on purchase intention in the Shopee marketplace among students at the University of Riau. The research method used is quantitative. The sample consisted of 384 respondents who are students of the University of Riau, selected using a non-probability sampling technique, specifically purposive sampling. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using simple and multiple linear regression with the SPSS version 25 software. The tests performed in this study included validity, reliability, multicollinearity, heteroscedasticity, simple linear regression, t-test, multiple linear regression, F-test, and coefficient of determination (R²). The results show that online customer reviews (X1) and price consciousness (X3) have a positive and significant influence on purchase intention (Y). Keywords: Online Customer Review, Price Consciousnes, Shopee, Marketplace